The Effect of Emoji Use on Recipients' Emotion Regulation under Social Media - Lin, Qianxi (International Journal of Social Sciences and Public Administration, 2025)
As society continues to develop and evolve, emojis are increasingly replacing certain expressions traditionally conveyed through plain text. This paper transitions from examining the impact of plain text on the receiver to analyzing how the inclusion of emojis in text regulates the receiver's emotions. The findings of this research not only enhance our understanding and utilization of emojis but also open new avenues for exploration in psychology and behavioral studies.